Changes in Teacher–Student Interaction Patterns in Digital Learning: Implications for Learning Motivation and Engagement - Ika Rahma (Archipel: Journal of Indonesian Interdisciplinary Studies, 2025)
This study examines changes in teacher-student interaction patterns in the context of digital learning and their impact on student motivation and engagement through a literature review approach. A systematic review of scientific publications from the past five years was conducted to identify the dynamics of technology-mediated pedagogical interactions and their consequences on student motivation and engagement in the learning process. The findings indicate that effective interactions in digital environments are positively correlated with student motivation and engagement, particularly through two-way communication, responsive feedback, and technology-based interactive strategies. Variations in pedagogical strategies and teachers' digital literacy readiness are key determinants of the quality of interactive relationships in digital learning. Furthermore, student engagement is measured through affective, cognitive, and behavioral indicators that are influenced by the quality of teacher-student interactions. The literature also indicates that challenges such as limited access to technology and lack of emotional support can hinder motivation and engagement. Thus, this study emphasizes the importance of strengthening pedagogical interactions in digital learning design to improve student learning outcomes. The implications of these findings are suggested as a reference for developing more humanistic and impactful digital education practices.